Actual vs. Ideal Attraction: Trends in the Mobility of Korean International Students - Ghazarian, Peter G. (Journal of International Students, 2014)
In the Republic of Korea (Korea), pressures emerging from the domestic education system seem to drive growing numbers of tertiary students abroad. This trend creates an outward flow of resources and has a number of impacts on Korean society. This study examines trends in the movement of tertiary students out of Korea from 2001 to 2010 and compares destinations’ actual market share with the Korean public’s ideal attraction. The results provide insight into the push-pull factors influencing Korean students’ destination choice and the influence of higher education policy in the global market for international students.